A qualitative study to explore dietary knowledge, beliefs, and practices among pregnant women in a rural health zone in the Democratic Republic of Congo - Benito Kazenza Maykondo; Christiane Horwood; Lyn Haskins; Sphindile Mapumulo; Mala Ali Mapatano; Branly Mbunga Kilola; Marc Bosonkie Mokanisa; Anne Hatloy; Vaughn M. John; Paulin Mutombo Beya Wa Bitadi (BMC, 2022)
Abstract Background A nutritious and healthy diet during pregnancy is essential for the health of both mother and baby. Inadequate dietary intake during pregnancy contributes to maternal malnutrition and can have lifelong effects on the health of the child. Maternal malnutrition is common in many low-income countries, including the Democratic Republic of Congo (DRC). Kwango province, DRC, has a high prevalence of malnutrition among all population groups, including macro and micronutrient deficiencies among pregnant women. The study aimed to explore the dietary knowledge and practices of a pregnant woman in this area. Methods This study adopted a qualitative approach using in-depth interviews (IDIs) with pregnant women and key informants, and focus group discussions (FGDs) with fathers and grandmothers in the community, to explore women's knowledge and practice about diet during pregnancy. Data were collected between January and April 2018. IDIs were conducted with pregnant women who were recruited at antenatal clinics during their second and third trimesters. IDIs were undertaken with selected key informants, who were health workers providing care to pregnant women, and included doctors, nurses, nutritionists, and community health workers. All IDIs and FGDs were audio-recorded, transcribed verbatim, and translated to English. The triangulation method and thematic analyses were used. Results Overall, women showed good general knowledge about nutrition and the need for increased and varied foods during pregnancy, but little technical knowledge about nutrients and sources of nutrition. Healthcare facilities, media, NGOs, and family members were the main sources of nutritional information. However, women were unable to put this knowledge into practice, primarily due to poverty and poor access to a variety of foods. The Popokabaka community accessed food from farming, fishing, and the market, although purchasing food was frequently unaffordable. Cassava flour was the most common daily food. Food taboos, traditional practices, and late ANC attendance were identified as factors that influenced dietary practices. Conclusions Various social, economic, and environmental factors within the local community influenced dietary practices among pregnant women in rural DRC. A comprehensive approach is required to improve nutrition, and address food insecurity, cultural practices and improve the health outcomes of both mother and child.